Pengujian Hubungan Reaktansi Induktif pada Induktor Terhadap Perubahan Frekuensi Sumber Arus dengan LED Sebagai Indikator - Alhidayatuddiniyah T W; Siwi Puji Astuti (UNIVERSITAS INDRAPRASTA PGRI, 2021)
The purpose of this study is to understand the working principle of the inductor component, especially the characteristics of the inductive reactance of the inductor using LED as an indicator. The research began by assembling a device, calculating the change in inductor impedance to changes in frequency using the inductor as a Low Pass Filter, then proceeding to investigate the relationship between AC current and voltage in the inductor. The results obtained that the magnitude of the current in the inductor is inversely proportional to the angular frequency of the AC current, while the voltage on the inductor is directly proportional to the magnitude of the angular frequency of the AC current. Based on the results of observations and calculations, different values are obtained, this can be due to an error in the ammeter, where the ammeter has the property of rectifying AC voltage to DC, so there is a possibility that only the peak signal is measured. And based on the linear graph only at frequencies of 50 Hz and 100 Hz, because at this frequency the waves still look perfect on the oscilloscope, while the other valley signals are cut off, the graph becomes non-linear.